Community-Based Interventions to Reach 95-95-95 for Children and Adolescents: An Exploratory Programmatic Review From Lesotho. (15th August 2018) - Amzel, Anouk; Srivastava, Meena; Isavwa, Anthony; Sanders, Jill; Tumbare, Esther; Membe, Ian; Mirembe, Justine; Ntjabane, Seema; Raliile, Peter; Mohoanyane, Matsitso; Ryan, Victoria
Abstract : Background: Viral suppression is the desired outcome for children and adolescents with HIV. In this article, data from districts supporting community interventions (implementation districts) were reviewed and compared with data from districts without community interventions (nonimplementation districts) to explore a potential correlation between community interventions and clinical outcomes. Setting: The study was based on data collected from facilities in 6 districts in Lesotho. Methods: Twelve-month retention, viral load coverage, and viral suppression data from patients with ART between ages 5 and 24 from facilities in both district types were collected retrospectively. Results: Implementation districts showed retention rates of 75%, with 5365 patients (47% of all patients on ART) having documented viral load results and 4641 (87%) being virally suppressed. Retention comparison demonstrated significantly higher rates in implementation districts (73%) as compared to (63%) in nonimplementation districts ( P = 0.023). Viral load coverage and suppression comparison found that implementation district hospitals reported 632 (37% of total on ART) patients with a documented viral load, with 539 (85%) virally suppressed, whereas nonimplementation district hospitals reported 220 (31%) patients with viral load results, of whom 181 (82%) were suppressed. Conclusions: Overall, retention rates in the implementation districts were reasonable and were significantly better than the rates in the nonimplementation districts.